Inhibition of BCL9 Modulates the Cellular Landscape of Tumor-Associated Macrophages in the Tumor Immune Microenvironment of Colorectal Cancer - Wei, Zhuang; Yang, Mengxuan; Feng, Mei; Wu, Zhongen; Rosin-Arbesfeld, Rina; Dong, Jibin; Zhu, Di (Frontiers in Pharmacology, 2021)
Tumor-associated macrophages (TAMs) are an indispensable part of tumor microenvironment (TME), and they likely play a negative rather than positive role in cancer treatment. However, the cellular landscape and transcriptional profile regulation of TAMs in the case of tumor gene inactivation or chemical interference remains unclear. The B-cell lymphoma 9/B-cell lymphoma 9-like (BCL9/BCL9L) is a critical transcription co-factor of β-catenin. Suppression of Bcl9 inhibits tumor growth in mouse models of colorectal cancer (CRC). Here, we studied the TAMs of CRC by single-cell sequencing. Bcl9 depletion caused macrophage polarization inhibition from M0 to M2 and changes the CRC TME, which further interferes with the inflammation of M0 and M1. The transcription factor regulating these processes may be related to the Wnt signaling pathway from multiple levels. Furthermore, we also found that the cells delineated from monocyte to NK-like non-functioning cells were significantly different in the BCL9-deprived population. Combining these data, we proposed a TAM-to-NK score to evaluate the dynamic balance in TME of monocyte/TAM cells and NK-like non-functioning cells in The Cancer Genome Atlas (TCGA) clinical samples to verify the clinical significance. We demonstrated that the cell type balance and transcription differences of TAMs regulated by BCL9-driven Wnt signaling affected immune surveillance and inflammation of cancer, ultimately affecting patients’ prognosis. We thereby highlighted the potential of targeting Wnt signaling pathway through cancer immunotherapy.